2011
DOI: 10.1590/s1807-59322011000200008
|View full text |Cite
|
Sign up to set email alerts
|

Fequency distribution of HLA DQ2 and DQ8 in celiac patients and first-degree relatives in Recife, northeastern Brazil

Abstract: AIMS:The aim of this study was to evaluate the frequencies of the HLA genotypes DQ2 and DQ8 and the alleles A1*05, A1*0201, B1*0201 and B1*0302 in individuals with celiac disease in Recife, northeastern Brazil.METHODS:HLA DQ2 and DQ8 genotyping was performed for 73 individuals with celiac disease and 126 first-degree relatives with negative transglutaminase serology. The alleles DQA1*05, DQA1*0201, DQB1*02 and DQB1*0302 were identified by sequencing using specific primers and the EU-DQ kit from the Eurospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 26 publications
3
15
1
4
Order By: Relevance
“…Additionally, in our study, when considering the presence of the DQ2.5 variant without association with DQ8, the frequency found in celiac patients was 75.1%, while in previous studies performed in the Southern and Northeastern regions of Brazil was 65.3% [24] and 68.5%, respectively [23]. The presence of DQ8 alone (i.e., without the concomitant presence of DQ2.5) among our celiac patients was 10.5%.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Additionally, in our study, when considering the presence of the DQ2.5 variant without association with DQ8, the frequency found in celiac patients was 75.1%, while in previous studies performed in the Southern and Northeastern regions of Brazil was 65.3% [24] and 68.5%, respectively [23]. The presence of DQ8 alone (i.e., without the concomitant presence of DQ2.5) among our celiac patients was 10.5%.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies performed in small series of celiac patients revealed that HLA-DQ2.5 and/or DQ8 were present in 93.1% of celiac patients in the Northeastern region of Brazil, where the miscegenation with Africans and Amerindians is more intense [23]. In the Southern region, where Caucasian ancestry predominates, the frequency of 91.1% was found [24].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that demonstrate that isolated DQB1*02 would confer a predisposition towards triggering CD (15,25,26,30,31,(36)(37)(38)(39), and the presence of isolated DQA1*05 would not (15,22,25). In our study, 1 % of celiac children and 1.4 % of adults presented isolated DQB1*02 compared to healthy controls (11.1 % of cases).…”
Section: Discussionmentioning
confidence: 40%
“…Castro-Antunes et al found genetic predisposition in 78.6% of the patients' relatives in the North East region (4) , and a study performed in the Center West region by Martins et al, described the DQ2 allele in 42% of the relatives, being DQ2 associated to DRB1*04 in 13% and DRB1*04 alone in 4.6% of the individuals (19) . However, since the studies were performed in relatives, it was not possible to detect the real genetic predisposition for CD in the Brazilian general population.…”
Section: Discussionmentioning
confidence: 96%